Where modern science and civilization meet Islamic values and epistemology: creative encounters - Solihu, Abdul Kabir Hussain (2010)
Modern science and civilization develop many things for human use and raise many critical questions which touch the core Islamic ethical and aesthetical values and its epistemology, leaving us with more doubts than ever before. Islam advanced a positive attitude towards science and civilization through its well established epistemology and value-based mechanism rooted in the Maqasid al-Shari‘ah (objectives of Islamic law). Based on this mechanism Islam creatively endorses whatever meets its standard and rejects whatever violates it. This creative encounter between Islam and modern science and civilization is explored in five broad integrated fronts: ethical, aesthetical, epistemological, eschatological and ontological fronts. The findings are published in four local and international refereed journals and in a book chapter.